An inquiry into the production and material-reality of hybridity through an analysis of where and when - Choudhury, Sanjukta (2025)
In this thesis, I assemble my inquiry into hybrid work in becoming inspired by new materialist thought, and thereafter in being moved along different directions. Structuring the thesis into three parts, each of which connect to each other laterally rather than hierarchically, I seek to map the inquiry which unfolded in a similar multi-directional, non-hierarchical way. And so, while this thesis contributes to academic scholarship on hybrid work, and more broadly, new ways of working, and in so doing, develops organisation theory on space and time, the writing of this inquiry hopes to leave that which is produced from its reading open-ended. I situate the inquiry with/in the post-pandemic world of work whereby hybrid work, commonly referred to as a way of working which entails splitting working at the office and home using technology, has been hailed as the ‘future of work’. In encountering only limited academic scholarship relating to hybrid work specifically, I move my inquiry towards developing an empirically informed understanding of hybrid work. Turning to related telework and broader new ways of working literature, I encountered recent sociomaterial perspectives which overcome dualist drawbacks of focusing either on people or technology by examining how both are entangled with each other in enactments of such ways of working. In seeking to continue the sociomaterial stream of research in my own inquiry into hybrid work, I encounter new materialist scholarship which extends an understanding of materiality beyond that of technology through a complete ontological (re)turn to matter. Through a new materialist perspective, I approach hybrid work as a phenomenon of human-nonhuman relations, and therein, seek to understand the materiality of hybrid work – how it is produced, and the material-realities it produces. In commencing my empirical research into the material-reality of hybrid work in one UK-based organisation called MCorp (a pseudonym), my inquiry unfolds across different directions through both my empirical encounters and further wanderings across different regions of literature. Specifically, my inquiry moves along the directions of space and time. Accordingly, I seek to understand the material production of hybrid work by addressing where hybrid work materialises and the time and temporality of how hybrid work unfolds in everyday life. Empirical inquiry was performed according to, what I have referred to as, an assemblage ethnography, which was informed by considerations of a post qualitative inquiry. This approach, which emphasises the intra-actions between the researcher and the researched for producing knowledge (Barad, 2003; 2007), was developed along the way as I realised a ‘pure’ traditional ethnography would not align with my ‘hybrid’ phenomenon of inquiry. And so, an emergent analysis of the space and time of hybrid work unfolded through my inquiry, details of which I assemble in my two empirical chapters. Accordingly, I render an analysis of MCorp’s spatial system of hybrid work according to Law and Mol’s (1994; 2001) topological shapes of region, network, fluid, and fire. This puts forth an understanding of hybrid spatiality of work which is produced by human-nonhuman agencies taking different shapes. Hybrid space, therefore, not only involves both fixing and moving work but also contingently transforming the materiality with/in which work takes place and making visible centres of presence through absence of certain relations. Along the temporal dimension, I render an analysis of four times: mechanical, elastic, infrastructured, and viscous, which emerges in MCorp, and consequently, affects how working and organising unfolds in their everyday hybrid organisational life through micropolitical dynamics between them. Such empirical analysis is put into conversation with existing organisation studies literature and theory on telework, new ways of working, space, and time for producing different understandings about these matters. Specifically, I propose that hybrid work is produced by the organising of paradoxes across topological shapes of hybrid space, through the micropolitics between different materialisations of time, which affect the everyday unfolding of material-realities of hybridity.